Blood pressure-to-height ratio for diagnosing hypertension in adolescents - Kristina Ambarita; Oke Rina Ramayani; Munar Lubis; Isti Ilmiati Fujiati; Rafita Ramayati; Rusdidjas Rusdidjas (Indonesian Pediatric Society, 2017)
Background Diagnosing hypertension in children and adolescents is not always straightforward. The blood pressure-to-height ratio (BPHR) has been reported as a screening tool for diagnosing hypertension.Objective To evaluate the diagnostic value of blood pressure-to-height ratio for evaluating hypertension in adolescents.Methods A cross-sectional study was conducted among 432 healthy adolescents aged 12-17 years in Singkuang, North Sumatera from April to May 2016. Blood pressure tables from the National High Blood Pressure Education Program (NHBPEP) Working Group on High Blood Pressure in Children and Adolescents were used as our standard of comparison. Sex-specific systolic and diastolic blood pressure-to-height ratios (SBPHR and DBPHR) were calculated. ROC curve analyses were performed to assess the accuracy of BPHR for discriminating between hypertensive and non-hypertensive adolescents. Optimal thresholds of BPHR were determined and validated using 2x2 table analyses.Results The accuracies of BPHR for diagnosing hypertension were > 90% (P<0.001), for both males and females. Optimal SBPHR and DBPHR thresholds for defining hypertension were 0.787 and 0.507 in boys, respectively, and 0.836 and 0.541 in girls, respectively. The sensitivities of SBPHR and DBPHR in both sexes were all >93%, and specificities in both sexes were all >81%. Positive predictive values for SBPHR and DBPHR were 38.7% and 45.2% in boys, respectively; and 55.9% and 42.4% in girls, respectively; negative predictive values in both sexes were all >97%, positive likelihood ratios in both sexes were all >5, and negative likelihood ratios in both sexes were all <1.Conclusion Blood pressure-to-height ratio is a simple screening tool with high sensitivity and specificity for diagnosing hypertension in adolescents.